Swear Words in “End of Watch” Movie Directed by David Ayer (A Socio-Pragmatics Study) - Sabanti, Mayanti A.; Malabar, Fahria; Bouti, Suleman (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this study is to examine the swear words uttered by all of the characters in the